2022
DOI: 10.1177/17562848221102307
|View full text |Cite
|
Sign up to set email alerts
|

The hospitalization burden of inflammatory bowel disease in China: a nationwide study from 2013 to 2018

Abstract: Background: The past decade has witnessed a dramatic increase in the number of patients with inflammatory bowel disease (IBD) in China. The nationwide burden of hospitalization remains unclear, however. We aimed to address this gap by conducting analysis using a nationwide database. Methods: Population-based hospitalization rates from 2013 to 2018 were calculated by extrapolating the number of patients in the database to the national level. Surgical rates, annual hospital charges, and length of stay were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…He et al gathered hospitalization data for patients with IBD in China from the Hospital Quality Monitoring System (HQMS) database from 2013 to 2018. According to their study, hospitalization rates of IBD patients increased from 2.20 (95% CI = 2.17, 2.22) to 3.62 (3.59, 3.65) per 100,000 inhabitants, and hospitalization costs associated with IBD reached $426 million in 2018 ( 33 ). The insufficient health care coverage system and uneven medical conditions exacerbate the financial pressures and difficulties in accessing health care faced by IBD patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…He et al gathered hospitalization data for patients with IBD in China from the Hospital Quality Monitoring System (HQMS) database from 2013 to 2018. According to their study, hospitalization rates of IBD patients increased from 2.20 (95% CI = 2.17, 2.22) to 3.62 (3.59, 3.65) per 100,000 inhabitants, and hospitalization costs associated with IBD reached $426 million in 2018 ( 33 ). The insufficient health care coverage system and uneven medical conditions exacerbate the financial pressures and difficulties in accessing health care faced by IBD patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the increasing hospitalization rates of patients with CD in China have caused a heavy economic burden [2]. A study conducted in China in a nationwide database showed that from 2013 to 2018, the hospitalization rates for CD in China increased from 2.20 to 3.62 per 100,000 individuals with an annual percentage of change of 10.68%, and the hospital charges for CD patients were $1631.15 (interquartile range (IQR) = $2230.79) in 2018 [2]. Because there are no specific clinical manifestations in the early stages of CD, its diagnosis is based on endoscopy, pathology, imaging and other comprehensive diagnoses, resulting in difficulties and delays in diagnosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that CD involved an inflammatory response caused by the combined action of multiple factors such as genetic susceptibility, environmental factors, gut microbes and immune responses [1]. In recent years, the increasing hospitalization rates of patients with CD in China have caused a heavy economic burden [2]. A study conducted in China in a nationwide database showed that from 2013 to 2018, the hospitalization rates for CD in China increased from 2.20 to 3.62 per 100,000 individuals with an annual percentage of change of 10.68%, and the hospital charges for CD patients were $1631.15 (interquartile range (IQR) = $2230.79) in 2018 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory gastrointestinal disorder, which affects 6.8 million people globally [ 1 ]. In China, the absolute number of hospitalized patients with IBD is estimated to reach 166,000 in 2018 [ 2 ]. Moreover, about one-third of patients with IBD develop a strictured disease phenotype during their lifetime [ 3 ].…”
Section: Introductionmentioning
confidence: 99%